2005
DOI: 10.1097/01.jom.0000165751.21088.46
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Safety Culture/Climate and Worker Compliance With Hazardous Drug Guidelines: Lessons From The Blood-Borne Pathogen Experience

Abstract: The Safety Culture paradigm offers many targets for intervention to enhance and promote worker compliance with safe HD handling practices thus mitigating internal exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
0
13
0
3
Order By: Relevance
“…Research has shown that increasing employee awareness of safety-related issues via training can improve the general safety climate in the workplace (e.g., McDiarmid & Condon, 2005;Williams, Purdy, Storey, & Nakhla, 2007). Similar to the safety climate, we expect that employees are likely to perceive a positive violence climate when they are informed about a comprehensive set of violence prevention policies.…”
Section: Work and Stress 119mentioning
confidence: 93%
See 1 more Smart Citation
“…Research has shown that increasing employee awareness of safety-related issues via training can improve the general safety climate in the workplace (e.g., McDiarmid & Condon, 2005;Williams, Purdy, Storey, & Nakhla, 2007). Similar to the safety climate, we expect that employees are likely to perceive a positive violence climate when they are informed about a comprehensive set of violence prevention policies.…”
Section: Work and Stress 119mentioning
confidence: 93%
“…In recent years, it has received a lot of research attention as safety climate is often regarded as a proactive approach to enhance and manage workplace safety. Indeed, studies have found that individual perceptions of safety climate not only work as the mechanism underlying the effects of safety training on worker compliance (McDiarmid & Condon, 2005), but they can also moderate the job insecurity-safety outcomes relationships (Probst, 2004). Additionally, individual perceptions of safety climate have been linked to important safety outcomes, including accidents (e.g., Hayes, Perander, Smecko, & Trask, 1998;Hofmann & Mark, 2006), injury (e.g., Huang, Ho, Smith, & Chen, 2006;Zacharatos, Barling, & Iverson, 2005), and physical and psychological strains (Goldenhar, Williams, & Swanson, 2003;Hayes et al, 1998).…”
Section: Safety and Violence Climatementioning
confidence: 96%
“…Many anticancer drugs are recognized genotoxic and carcinogenic chemicals, 41 and the adverse reproductive effects of cytotoxic drugs have been well-characterized. 2 …”
Section: Commentmentioning
confidence: 99%
“…Many anticancer drugs are recognized genotoxic and carcinogenic chemicals, 41 and the adverse reproductive effects of cytotoxic drugs have been well-characterized. 2 In summary, our study found that shift work and physical factors were not strong predictors of preterm birth and part-time work was inversely associated with preterm birth.…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%